2019
DOI: 10.3390/genes10050367
|View full text |Cite
|
Sign up to set email alerts
|

An Entamoeba-Specific Mitosomal Membrane Protein with Potential Association to the Golgi Apparatus

Abstract: The aerobic mitochondrion had undergone evolutionary diversification, most notable among lineages of anaerobic protists. Entamoeba is one of the genera of parasitic protozoans that lack canonical mitochondria, and instead possess mitochondrion-related organelles (MROs), specifically mitosomes. Entamoeba mitosomes exhibit functional reduction and divergence, most exemplified by the organelle’s inability to produce ATP and synthesize iron-sulfur cluster. Instead, this organelle is capable of sulfate activation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…Similar to Giardia, it would not be surprising if future studies reveal a minimalist mechanism of protein targeting and import in this relic mitochondria of Entamoeba that is accompanied by components unique to its genus. This is supported by discoveries of several Entamoeba-specific mitosomal membrane proteins [55] such as the β-barrel outer membrane protein MBOMP30 [25], and the transmembrane protein ETMP30 [29].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Similar to Giardia, it would not be surprising if future studies reveal a minimalist mechanism of protein targeting and import in this relic mitochondria of Entamoeba that is accompanied by components unique to its genus. This is supported by discoveries of several Entamoeba-specific mitosomal membrane proteins [55] such as the β-barrel outer membrane protein MBOMP30 [25], and the transmembrane protein ETMP30 [29].…”
Section: Discussionmentioning
confidence: 85%
“…As described previously [29], IFA of amoebic trophozoites was performed by double staining with anti-HA monoclonal antibody (clone 11MO, Covance, Princeton, NJ, USA) to detect hemagluttinin (HA)-tagged proteins and anti-adenosine-5 -phosphosulfate kinase (APSK) (EHI_179080, a mitosomal matrix protein) polyclonal rabbit antiserum [21] to label mitosomes. Cells that expressed HA-tagged proteins were analyzed according to the following three localization categories: mitosome, mitosome and cytosol, and cytosol.…”
Section: Immunoflourescence Assay (Ifa)mentioning
confidence: 99%
“…To verify the localization of these proteins, we performed immunofluorescence assay. Micrographs of cells stained with anti-HA antibody showed mostly vesicular signals of TSPAN1 and TSPAN2 (Figure 6b), rather than the punctate signal pattern associated with mitosome localization [32,42,43,44,45,46,47]. The anti-HA signals did not colocalize with the mitosome marker (anti-APSK: mitosomal matrix enzyme, [35]) in double-stained cells (Figure 6b, top panel), suggesting TSPAN1 and TSPAN2 are not localized to mitosomes.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, vestigial organelle functionally related to mitochondria, the mitosome, has been reported (Tovar, Fischer, & Clark, 1999). Recently, an in silico and immune‐electron microscopy study reported a new lineage protein specific of mitosomes, previously localized in Golgi‐like vacuoles, suggesting a relation between both structures (Santos, Hanadate, Imai, & Nozaki, 2019).…”
Section: Discussionmentioning
confidence: 99%